Plaster material, plaster, and method for preparing plaster material

A plaster material using raw lime, glass powder, and high-CA-ion-containing solution addresses limitations in existing plasters by enhancing strength and durability, suitable for diverse applications.

JP2025016204APending Publication Date: 2025-01-31株式会社濑户漆喰本铺 +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023119332
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

Existing plaster materials lack improvements to expand their scope and application, particularly in terms of strength, durability, and versatility.

Method used

A plaster material composed primarily of raw lime and/or slaked lime, glass powder as an aggregate, and a high-CA-ion-containing aqueous solution, with specific ratios and water content determined by flow value correlations, enhances strength and adhesion.

Benefits of technology

The new plaster material exhibits improved bending and compression strength, faster drying, and enhanced waterproofness, making it suitable for various applications including top coats and exterior finishes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016204000001_ABST
    Figure 2025016204000001_ABST
Patent Text Reader

Abstract

To provide a novel plaster material that is useful for expanding a range of uses and applications of a plaster, a plaster made by hardening the plaster material, and a method for preparing the plaster material.SOLUTION: A plaster material according to the present invention contains, as main components, quicklime and / or hydrated lime, aggregate, and water, wherein the aggregate is a glass powder. A high-Ca ion-containing aqueous solution having a Ca ion concentration of 2 to 20 g / L can be suitably used as the water. In the plaster material according to the present invention, a weight ratio of the quicklime and / or the hydrated lime to the aggregate is preferably 1:1 to 1:4.SELECTED DRAWING: Figure 9
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a plaster material, a plaster obtained by hardening the plaster material, and a method for preparing the plaster material. [Background technology]

[0002] Plaster is made by mixing slaked lime with hemp fiber, straw fiber, adhesives made from herbs and seaweed, and water, and is known as a coating material that hardens while absorbing carbon dioxide (air-hardening). In recent years, plaster mixed with synthetic resins and pigments has been commercialized, and attempts are being made to expand the range and uses of plaster, such as improving the strength of plaster, improving the strength expression, or developing new products that focus on the original properties of plaster, such as its moisture-regulating function and formaldehyde adsorption and decomposition function.

[0003] For example, Patent Document 1 proposes a plaster composition containing γ-type 2CaO·SiO2 and calcium hydroxide as a plaster composition that is less likely to crack or flake and has improved strength development. Patent Document 2 also proposes a plaster adhesive hardening material that hardens to high strength both in air and water and can be used in a wider range of applications, and is made by blending slaked lime or quicklime, or a mixed powder of these, with one or more components selected from an alkali silicate component and an alkaline earth metal salt as the main raw material.

[0004] The present inventors have developed a plaster material that uses a high Ca ion-containing aqueous solution as a plaster material with excellent bending strength and compressive strength (see, for example, Patent Document 3). In addition, they have developed a plaster material that has high strength and toughness and is lightweight, and a plaster material and plaster panel that use the same, which incorporate bamboo powder (see, for example, Patent Document 4). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-104039 A [Patent Document 2] JP 2000-72520 A [Patent Document 3] Patent No. 4843733 [Patent Document 4] Patent No. 6524857 Summary of the Invention [Problem to be solved by the invention]

[0006] As mentioned above, various attempts have been made to expand the range and applications of plaster, but further improvements are expected to expand the uses and applications of plaster.

[0007] An object of the present invention is to provide a novel plaster material that contributes to expanding the uses and applications of plaster, a plaster obtained by hardening the plaster material, and a method for preparing the plaster material. [Means for solving the problem]

[0008] The present invention relates to a plaster material containing quicklime and / or slaked lime, aggregate, and water as main components, the aggregate being glass powder.

[0009] The plaster material according to the present invention is characterized in that the water is a high-Ca-ion-containing aqueous solution that contains calcium ions at a high concentration, and the Ca-ion concentration of the high-Ca-ion-containing aqueous solution is 2 to 20 g / L.

[0010] The plaster material according to the present invention is characterized in that the weight ratio of the quicklime and / or slaked lime to aggregate is 1:1 to 1:4.

[0011] In the plaster material according to the present invention, the quicklime and / or slaked lime is obtained by burning oyster shells at 900 to 1200°C.

[0012] The present invention is a topcoat material for plaster made of the above-mentioned plaster material.

[0013] The present invention relates to plaster produced by mixing and hardening the plaster material.

[0014] The plaster of the present invention is characterized in that its water permeability is half or less compared to plaster made by mixing and hardening a plaster material using lime sand as aggregate.

[0015] The present invention is a method for preparing a plaster material, which is characterized by obtaining a correlation between the water-lime ratio of the plaster material and a flow value in a flow test conforming to JIS R5201, and determining the amount of water to be added based on the flow value. Effect of the Invention

[0016] According to the present invention, it is possible to provide a novel plaster material that contributes to expanding the uses and applications of plaster, a plaster obtained by hardening the plaster material, and a method for preparing the plaster material. [Brief description of the drawings]

[0017] [Figure 1] 1 shows the results of measuring the weight increase / decrease rate of the glass powder plaster described in Example 1 of the present invention. [Diagram 2] 1 is a measurement result of the volumetric increase / decrease rate of the glass powder plaster described in Example 1 of the present invention. [Diagram 3] 1 is a density measurement result of the glass powder plaster described in Example 1 of the present invention. [Figure 4] 1 shows the results of measuring the bending strength and compressive strength of the glass powder plaster described in Example 1 of the present invention. [Diagram 5] FIG. 2 is a diagram showing the relationship between the water-lime ratio and the flow value of the glass powder plaster material described in Example 1 of the present invention. [Figure 6] 1 shows the results of measuring the weight increase / decrease rate of the glass powder-rich Ca plaster described in Example 2 of the present invention. [Figure 7] 1 shows the volumetric increase / decrease rate measurement results of the glass powder high Ca plaster described in Example 2 of the present invention. [Figure 8] 1 is a result of measuring the density of the glass powder-rich Ca plaster described in Example 2 of the present invention. [Figure 9]1 shows the results of measuring the bending strength and compressive strength of the glass powder high Ca plaster described in Example 2 of the present invention. [Figure 10] FIG. 1 is a diagram showing the relationship between the Ca ion concentration and the flow value of the glass powder high Ca plaster material described in Example 2 of the present invention. [Figure 11] 1 shows the results of a water permeability test of the glass powder high Ca plaster described in Example 2 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] In the present invention, the various types of plaster are defined as follows. As with conventional plaster, plaster using water as the liquid for kneading plaster material containing lime and fine aggregate is called ordinary plaster, plaster using an aqueous solution containing high Ca ions (high Ca ion-containing aqueous solution) instead of water is called high Ca plaster, plaster material containing glass powder using water as the liquid for kneading plaster material containing glass powder is called glass powder plaster, and plaster material containing glass powder using an aqueous solution containing high Ca ions as the liquid for kneading plaster material containing glass powder is called glass powder high Ca plaster. Plaster material refers to the material before each material is kneaded, and also includes the plaster composition in which each material is kneaded. The hardened plaster composition is called plaster.

[0019] The plaster material of the first embodiment of the present invention is a glass powder plaster material whose main components are quicklime and / or slaked lime, aggregate, and water, and the aggregate is glass powder. This plaster material is characterized in that it contains glass powder as aggregate. In addition to the above components, this plaster material may also contain hemp fiber or straw fiber (susa), adhesives obtained from herbs or seaweed, or adhesives made of synthetic resins, which are generally used in plaster.

[0020] In the present plaster material, quicklime, slaked lime, or a mixture of quicklime and slaked lime can be used as the lime. Burned shells such as oyster shells and scallop shells can also be used as the quicklime or slaked lime material.

[0021] The material of the glass powder is not particularly limited, and various glass powders such as optical glass, soda lime glass, and white plate glass can be used. Optical glass is used for lenses used in optical instruments. Soda lime glass is also called soda lime glass and is used for window glass, glass tableware, automotive glass, magnifying glasses, etc. White plate glass is used for liquid crystal panels, surveying instruments, copy machines, tempered glass, etc. The glass powder may consist of one type of glass powder or may be a mixture of two or more types of glass powder.

[0022] The primary particle size of the glass powder is not particularly limited, but glass powder of about 0.1 to 1 mm can be used. When the plaster material is used as a topcoat material, glass powder with a small particle size is preferable, and glass powder with a primary particle size of about 0.5 to 100 μm can be suitably used.

[0023] Glass powder can be produced by crushing glass, or glass powder generated during the manufacturing process of glass products, such as during polishing, can be used. For example, lens powder generated during the lens processing process is optical glass powder and is usually disposed of, but it can be effectively utilized by using it as a raw material for plaster material.

[0024] Lens powder and the like generated in the lens processing process are usually discharged in a state mixed with water, but the glass powder used in this plaster material may be such glass powder mixed with water, dehydrated glass powder mixed with water, or dried glass powder mixed with water. If necessary, the moisture content of the glass powder is not particularly limited. Dehydrated and dried glass powders are often in the form of lumps, and it is preferable to crush them before use.

[0025] This plaster material is mainly composed of quicklime and / or slaked lime, glass powder as aggregate, and water, so if glass powder with a different moisture content is used, the water-lime ratio will vary and the quality of the plaster will be inconsistent. This can be solved by obtaining the correlation between the water-lime ratio of the plaster material and the flow value in a flow test based on JISR5201, and determining the amount of water to be added based on the flow value. This will be described later.

[0026] The more the glass powder content of the plaster material is, the faster it dries when hardened and the greater its density becomes. Also, the more the glass powder content is, the easier it is for neutralization to proceed, and the greater the strength becomes.

[0027] The content of glass powder in this plaster material is preferably a weight ratio of lime:glass powder = 1:1 to 1:4, and more preferably a weight ratio of lime:glass powder = 1:3 to 1:4. This weight ratio of lime:glass powder is the mixing ratio. If the mixing ratio is less than 1:1, the influence of the lime in the plaster is large and cracks are likely to occur. On the other hand, if the mixing ratio exceeds 1:4, the binding strength between the lime and aggregate in the plaster is weak, and there is a tendency for the strength to be low and for the plaster to become brittle.

[0028] The plaster material may be a mixture of lime, glass powder, and water when used, or may be a mixture of lime, glass powder, and water in advance (a glass powder plaster composition). The mixture of lime, glass powder, and water in advance is stored in an airtight package, and is remixed when used.

[0029] The plaster composition obtained by kneading the plaster material having the above-mentioned composition is fine and smooth, and the plaster composition having a mixing ratio of 1:3 in particular is very smooth, easy to apply, and has very good adhesion. Therefore, it can be suitably used as a topcoat material. Furthermore, the glass powder plaster obtained by hardening this plaster composition has superior strength compared to ordinary plaster. Furthermore, the glass powder plaster obtained by hardening this plaster composition has excellent waterproofing properties, and the glass powder plaster having a mixing ratio of 1:3 in particular is almost impermeable to water, so it can be suitably used as a finishing material for exterior walls and wet areas.

[0030] The plaster material of the second embodiment of the present invention is a plaster material in which the water of the plaster material of the first embodiment of the present invention is replaced with a high Ca ion-containing aqueous solution. That is, the plaster material of the present invention is a glass powder high Ca plaster material mainly composed of quicklime and / or slaked lime, glass powder as an aggregate, and a high Ca ion-containing aqueous solution. Here, the high Ca ion-containing aqueous solution refers to a liquid containing a high concentration of Ca ions. Note that, like the plaster material of the first embodiment of the present invention, in addition to the above components, this plaster material may also contain hemp fiber or straw fiber (susa), adhesives obtained from herbs or seaweed, or adhesives made of synthetic resins, which are generally used in plaster.

[0031] The solubility of quicklime (CaO) and slaked lime (Ca(OH)2) in water is about 0.2%. In the plaster material of this embodiment, CaO and Ca(OH)2 dissolved at more than 0.2% are used. For this reason, for example, a stock solution is first prepared by dissolving CaO in an acetic acid solution or the like, which is easy to dissolve CaO in.

[0032] Then, this stock solution or an aqueous solution obtained by diluting this stock solution with water is prepared and used as the mixing water for the plaster material. The aqueous solution used for mixing contains Ca ions at a high concentration, so in the present invention it is called a high Ca ion-containing aqueous solution. The water in the high Ca ion-containing aqueous solution is not particularly limited, and may be any of tap water, ionized water, and pure water.

[0033] For example, when a 10% acetic acid solution is used as the high Ca ion-containing aqueous solution, it is possible to dissolve CaO at room temperature at a weight percentage concentration of about 3.2% (32 g / L) on a Ca basis. If it is difficult to dissolve CaO or Ca(OH)2, sodium bicarbonate (NaHCO3) can be added. In addition to the acetic acid solution, an acidic aqueous solution such as a citric acid solution or a formic acid solution may be used to dissolve CaO and / or Ca(OH)2. However, considering dissolving ability, an acetic acid solution is preferred. The pH of the high Ca ion-containing aqueous solution can also be adjusted when used.

[0034] The CaO and / or Ca(OH)2 used in preparing the high Ca ion-containing aqueous solution is not limited to a specific CaO and / or Ca(OH)2, and oyster shell powder calcined at 900 to 1200°C can be used as shown in the examples described later. Other shells can also be calcined and used instead of oyster shells.

[0035] Glass powder high-Ca plaster obtained by using a high-Ca ion-containing aqueous solution has higher bending strength and compressive strength than conventional plaster, and has excellent waterproofing. The amount of Ca ions in the high-Ca ion-containing aqueous solution is not limited to a specific value, and a solution containing Ca ions of about 2 to 20 g / L can be used, with a Ca ion concentration of 6 to 20 g / L being preferred, and from the perspective of overall softness, strength, physical properties, neutralization, etc., and also from the standpoint of economy, a Ca ion-containing aqueous solution containing Ca ions of 8 to 10 g / L is more preferred.

[0036] In the present plaster material containing a high Ca ion-containing aqueous solution, the content of the glass powder is preferably a mixing ratio of 1:1 to 1:4, more preferably 1:3 to 1:4, as in the plaster material of the first embodiment.

[0037] The plaster material may be prepared by storing lime, glass powder, and high Ca ion-containing aqueous solution separately and kneading them together when used, or it may be prepared by kneading lime, glass powder, and high Ca ion-containing aqueous solution in advance (glass powder high Ca plaster composition). Note that the pre-kneaded mixture of lime, glass powder, and high Ca ion-containing aqueous solution is stored in an airtight package and is kneaded again when used.

[0038] The plaster material having the above-mentioned structure is fine and smooth, like the plaster material of the first embodiment, and in particular the glass powder high Ca plaster composition with a mixing ratio of 1:3 is very smooth, easy to apply, and has very good adhesion. Therefore, it can be suitably used as a topcoat material. In addition, the glass powder high Ca plaster obtained by hardening this plaster composition has excellent waterproofing properties, and in particular the glass powder high Ca plaster with a lime ratio of 1:3 is almost impermeable to water, so it can be suitably used as a finishing material for exterior walls and wet areas. In addition, the glass powder high Ca plaster obtained by hardening this plaster composition has excellent bending strength and compressive strength.

[0039] Next, one embodiment of the method for preparing the plaster material according to the present invention will be described. The main components of this plaster material are quicklime and / or slaked lime, glass powder as aggregate, and water or a high Ca ion-containing aqueous solution. As mentioned above, the glass powder used in this plaster material has various forms and does not have a constant moisture content. If the moisture content of the glass powder differs, the water-lime ratio of the plaster material will naturally differ, and the quality of the plaster will also be inconsistent. In this preparation method, the quality of the plaster is stabilized by the following method.

[0040] The correlation between the water-lime ratio of the plaster material and the flow value in a flow test conforming to JIS R 5201 is obtained, and the amount of water to be added is determined based on the flow value. Specific examples are described in the Examples below. The water-lime ratio is the amount of water relative to lime (weight ratio x 100%).

[0041] The method of obtaining the correlation between the water-lime ratio of the plaster material and the flow value in a flow test conforming to JIS R5201 and determining the amount of water to be added based on the flow value can be applied even if the type of glass powder is changed, and can also be applied when a high Ca ion-containing aqueous solution is used as the water.

[0042] When using different types of glass powder, it is necessary to obtain in advance the correlation between the water-lime ratio of the plaster material using it and the flow value in a flow test conforming to JIS R5201, and when using a high Ca ion containing aqueous solution, it is necessary to obtain in advance the correlation between the water-lime ratio of the plaster material using it and the flow value in a flow test conforming to JIS R5201, and then use these.

[0043] Although the preferred embodiment has been described above, a person skilled in the art will easily imagine various changes and modifications within the obvious scope upon reading this specification. Therefore, such changes and modifications are interpreted as falling within the scope of the invention as defined by the claims. EXAMPLES

[0044] Example 1: Glass powder plaster material and glass powder plaster The method for preparing a typical glass powder plaster material is shown below. The lime used was the quicklime shown in Table 1 (manufactured by Nakayama Sekki Kogyo Co., Ltd.; particle size 0.15 mm or less). [Table 1]

[0045] The glass powder used was lens powder generated during the processing of optical glass lenses. The optical glass lens used here is an environmentally friendly glass known as eco-glass (ECO OPTICAL GLASS), a glass material whose main component is silicon and does not contain lead or arsenic. The primary particle size of the lens powder was measured by photographing it with an electron microscope, and the particle size measured was found to be 0.5 x 1.0 μm for the smallest particles, 70 x 80 μm for the largest, and 5 to 10 x 10 to 20 μm on average, with the particle surfaces being jagged.

[0046] The specific gravity ρ of the lens powder was measured to be 2.64 g / cm 3 This value is the same as the specific gravity of typical sandstone and sand, which is 2.65 to 2.67 g / cm 3The lens powder contained a small amount of water and was in the form of granules (aggregates), so after drying, the powder was crushed by hand and passed through a 0.5 mm sieve, and the material that passed through the sieve was used.

[0047] A glass powder plaster material (glass powder plaster composition) was obtained by kneading 100 parts by weight of lime, 300 parts by weight of glass powder, and 130 parts by weight of water. The plaster material had a mixing ratio of 1:3 and a water-lime ratio of 130%. In the same manner, the mixing ratio of lime:glass powder was changed from 1:1 to 1:4, and the water-lime ratio was changed from 120 to 240%, to obtain a glass powder plaster material (glass powder plaster composition).

[0048] The glass powder plaster test specimen was prepared as follows. The glass powder plaster composition obtained by the above procedure was poured into a triple-contiguous formwork until it was about half full, and then evenly poked with a ram so that the glass powder plaster composition spread to every corner of the formwork. The glass powder plaster composition was then poured into the formwork until it was full, and the ram was poked evenly until the bottom of the ram was 1 / 3 the depth of the previous one. The glass powder plaster composition was further poured in until the surface of the formwork was hidden, and the formwork was left for several hours. After that, the top of the formwork was cut with a parallel rod, removed from the formwork, placed in a curing case, and cured in air for a specified number of days in an air curing room to obtain a test specimen. The test specimen was a rectangular column of 40 x 40 x 160 mm.

[0049] The results of measuring the weight increase / decrease rate, volume increase / decrease rate, and density of the glass powder plaster are shown in Figs. 1 to 3. The indications in the key explanations in Figs. 1 and 2 refer to the mix ratio and the test specimen number. For example, 1:2-2 refers to the second test specimen with a mix ratio of 1:2. The weight increase / decrease rate was the weight ratio after 35 to 37 days of air curing to the weight of the test specimen at the time of removal from the form. The density was calculated by dividing the weight of the test specimen after 40 days of air curing by the volume measured using a digital caliper for the length, width, and height of the test specimen.

[0050] As shown in Figure 1, the weight increase / decrease rate was not greatly affected by the mix ratio, showing a similar decrease curve, and the weight decrease rate of the test specimen after 35 days of air curing was approximately 24 to 28%. The volume increase / decrease rate decreased slightly with the number of days elapsed, regardless of the mix ratio, and the volume shrinkage rate of the test specimen after 35 days of air curing was -4% when the mix ratio was 1:2, as shown in Figure 2, but was -2 to -0.5% for the others. The density of the glass powder plaster increased in proportion to the glass powder mix ratio, as shown in Figure 3, and was approximately 1.16 g / cm3 when the mix ratio was 1:1. 3 , the blend ratio is 1:4, about 1.34g / cm 3 It was.

[0051] The results of the strength test are shown in Figure 4. The test specimens were cured for 40 days. The strength test was conducted according to JISA1171 (Test method for polymer cement mortar).

[0052] As shown in Figure 4, the bending strength is about 0.23 N / mm when the compounding ratio is 1:1. 2 , with a mixing ratio of 1:4, it is approximately 0.96N / mm 2 The compressive strength increased in proportion to the mix ratio. As shown in Figure 4, the compressive strength was 0.8 N / mm when the mix ratio was 1:2. 2 However, the compounding ratio was 1.1, which was about 1.28N / mm 2 , with a compounding ratio of 1.4, it is approximately 1.62N / mm 2 Overall, the increase was proportional to the blend ratio.

[0053] Figure 5 shows the flow values ​​(mm) obtained when the mixing ratio was 1:3 and the water-lime ratio of the plaster material was changed in the range of 80 to 260%. The flow values ​​were obtained in accordance with the flow test specified in JIS R5201. Specifically, the flow values ​​were obtained by the following procedure. A PVC pipe with an inner diameter of 35 mm and a height of 50 mm was placed on a table, and the plaster composition was gently filled into the PVC pipe with a spoon until it was full. The plaster composition in the PVC pipe was then evenly poked 15 times with a poker. The raised plaster composition at the top end of the PVC pipe was then cut and flattened using a poker, and the PVC pipe was quickly and quietly pulled out. The maximum diameter of the plaster composition spread on the table and the diameter at a right angle to that diameter were measured, and the average value was taken as the first test. The same test was repeated twice, and the average value of the first and second tests was taken as the flow value.

[0054] It can be seen from Figure 5 that the flow value increases exponentially as the water-lime ratio increases. The relationship between the water-lime ratio and the flow value in Figure 5 is expressed by Equation (1). Y = 13.55exp(0.0082X) (1) Where Y: flow value (mm) X: water-lime ratio (%)

[0055] From this result, when the water-lime ratio is 130%, the flow value is 39.35 (mm). Therefore, when the moisture content of the glass powder is unknown and a plaster material with a water-lime ratio of 130% is to be manufactured, water should be added so that the flow value becomes 39.35 (mm).

[0056] Example 2: Glass powder high Ca plaster material and glass powder high Ca plaster The method for preparing the glass powder-rich Ca plaster material is as follows. 100 parts by weight of quicklime (manufactured by Nakayama Sekki Kogyo Co., Ltd.; particle size 0.15 mm or less) shown in Table 1, 300 parts by weight of the glass powder shown in Example 1, and 200 parts by weight of a high Ca ion-containing aqueous solution were mixed to obtain a glass powder-rich Ca plaster material. The high Ca ion concentrations were 0, 4, 8, 12, 16, and 20 g / L. The glass powder-rich Ca plaster specimens were prepared in the same manner as the glass powder plaster described in Example 1.

[0057] The high Ca ion-containing aqueous solution was prepared as follows. 100 g of acetic acid (1st grade, manufactured by Wako Pure Chemical Industries, Ltd., code No. 014-00266) was added to 900 g of pure water to obtain an aqueous solution of acetic acid (10% by weight concentration), and 30 g of white powder obtained by baking oyster shells at 1200 ° C was added in several batches and completely dissolved. After leaving this solution for half a day, the supernatant was collected and used as a high Ca ion-containing aqueous solution (stock solution). Water was added to the stock solution to obtain a high Ca ion-containing aqueous solution. The baking temperature of the oyster shells can be 900 to 1200 ° C. Table 2 shows the results of the component analysis of the white powder obtained by baking oyster shells at 1200 ° C.

[0058] [Table 2]

[0059] The measurement results of the weight change rate, volume change rate, and density of the glass powder high-Ca plaster are shown in Figures 6 to 8. The definitions and measurement procedures of the weight change rate, volume change rate, and density are the same as those of the glass powder plaster described in Example 1. The weight change rate and volume change rate were measured after 30 days of air curing, and the density was measured after 35 days of air curing.

[0060] As shown in FIG. 6, the weight increase / decrease rate was approximately -27.5% when the Ca ion concentration was 0 g / L and approximately -21.6% when the Ca ion concentration was 20 g / L, showing a tendency for the rate of decrease to decrease as the Ca ion concentration increased.

[0061] As shown in FIG. 7, the volumetric increase / decrease rate was approximately -0.6% when the Ca ion concentration was 0 and approximately -8.0% when the Ca ion concentration was 20 g / L, showing a tendency for the volumetric decrease rate to increase as the Ca ion concentration increased.

[0062] As shown in Figure 8, the density is approximately 1.24 g / cm when the Ca ion concentration is 0 g / L. 3 , Ca ion concentration is 20g / L and the concentration is about 1.50g / cm 3 The density increased with increasing Ca ion concentration.

[0063] The bending strength and compressive strength are shown in Figure 9. The bending strength was about 0.6 N / mm when the Ca ion concentration was 0 g / L. 2 , Ca ion concentration is 20g / L and the resistance is about 0.92N / mm 2 and increased with increasing Ca ion concentration. The compressive strength was about 1.36 N / mm at a Ca ion concentration of 0 g / L. 2 At a Ca ion concentration of 12 g / L, the resistance is approximately 1.5 N / mm 2 , Ca ion concentration is 20g / L and the resistance is about 2.13N / mm 2 The compressive strength increased rapidly after the Ca ion concentration reached 12 g / L.

[0064] The relationship between Ca ion concentration and flow value is shown in Figure 10. This glass powder high Ca plaster composition has a mixing ratio of 1:3 and a water-lime ratio of 200%. The flow test was carried out using two types of PVC pipes with diameters (inner diameters) of 55mm and 35mm in the same manner as in Example 1. The tendency of the curves showing the relationship between Ca ion concentration and flow value was very similar for the PVC pipes with diameters of 55mm and 35mm, and in both cases the flow value increased in proportion to the Ca ion concentration.

[0065] The flow value when the Ca ion concentration was 20g / L was 1.3 times that when the inner diameter was 55mm, and about 1.7 times when the inner diameter was 35mm, compared to the flow value when the Ca ion concentration was 0g / L. This is thought to be because Ca ions are divalent cations, so the ions repel each other like magnets, softening the plaster composition.

[0066] The permeability test of the glass powder high Ca plaster was carried out as follows. A glass powder high Ca plaster composition with a mix ratio of 1:3, water-lime ratio of 200%, and Ca ion concentration of 6g / L was poured into a formwork, and the formwork was removed and the composition was left to cure in air for 30 days to obtain a glass powder high Ca plaster. A transparent acrylic pipe was set up on top of the glass powder high Ca plaster measuring 100mm long x 100mm wide x 10mm thick, and the connection between the transparent acrylic pipe and the glass powder high Ca plaster was sealed with a caulking agent to prevent water from leaking from the connection, to produce a permeability test device.

[0067] A transparent acrylic pipe was filled with 50 cm of water, and the time it took for this 50 cm of water to permeate the glass powder high-Ca plaster was measured. For comparison, a high-Ca plaster composition was used that used lime sand as aggregate, had a mix ratio of 1:3, a water-lime ratio of 130%, and a Ca ion concentration of 6g / L, was poured into a formwork, and the formwork was removed and cured in air for 30 days.

[0068] The test results are shown in Figure 11. As shown in Figure 11, the time required for water to pass through a height of 50 cm was approximately 1,900 min for the glass powder high-Ca plaster and 925 min for the high-Ca plaster. As can be seen from this, the water permeability rate of the glass powder high-Ca plaster is approximately half that of the high-Ca plaster. The difference between the glass powder high-Ca plaster and the high-Ca plaster is the aggregate, and it can be said that the difference in water permeability rate is due to the difference in particle size between the glass powder and the lime sand. The glass powder high-Ca plaster has very fine flow paths for water to pass through, and depending on the level of contamination of the water being passed through, it may barely let water through.

Claims

1. A plaster material comprising quicklime and / or slaked lime, aggregate and water as main components, the aggregate being glass powder.

2. The water is a high Ca ion-containing aqueous solution containing calcium ions at a high concentration, The plaster material according to claim 1, characterized in that the Ca ion concentration of the high Ca ion-containing aqueous solution is 2 to 20 g / L.

3. The plaster material according to claim 1 or 2, characterized in that the weight ratio of the quicklime and / or slaked lime to aggregate is 1:1 to 1:

4.

4. The plaster material according to claim 1 or 2, characterized in that the quicklime and / or slaked lime is obtained by calcining oyster shells at 900 to 1200°C.

5. A plaster topcoat material comprising the plaster material according to claim 1 or 2.

6. A plaster obtained by mixing and hardening the plaster material according to claim 1 or 2.

7. The plaster according to claim 6, characterized in that the water permeability is half or less compared to that of plaster made by mixing and hardening a plaster material using lime sand as aggregate.

8. A correlation between the water-lime ratio of the plaster material according to claim 1 or 2 and a flow value in a flow test in accordance with JIS R5201 is obtained, 3. The method for preparing a plaster material according to claim 1 or 2, characterized in that the amount of water to be added is determined based on the flow value.

Citation Information

Patent Citations

  • JP1973043733A

  • Lime plaster-containing adhesive and hardening material

    JP2000072520A

  • Composition for mortar

    JP2006104039A

  • Plaster materials, plaster and plaster panels

    JP6524857B2